2002
DOI: 10.1002/syn.10145
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone (DHEA) such as 17β‐estradiol prevents MPTP‐induced dopamine depletion in mice

Abstract: Previous work from our laboratory has shown prevention of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced striatal dopamine (DA) depletion in mice by 17beta-estradiol, progesterone, and raloxifene. Dehydroepiandrosterone (DHEA), a neurosteroid, was shown to have neuroprotective activities in various paradigms of neuronal death but its effect in vivo in mice on MPTP toxicity has not been reported. We investigated the effects of 17beta-estradiol (2 microg/day) and DHEA (3 mg/day) for 5 days before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 35 publications
5
50
1
8
Order By: Relevance
“…Although BFP contains phytoestrogens such as ginseng 37) that may act similarly to estrogen, which has been shown to prevent neuronal degeneration caused by increased oxidative stress 38) and apoptosis 39) ; other component herbs of BFP may act through different mechanisms, the details of which remain to be elucidated. Consistent with our research, TH and DAT gene expression 40,41) and protein patterns 41,42) of dopaminergic neurons have also been described by the other researchers. The intensity of TH-and DAT-immunoreactive dopaminergic cell bodies and terminals was also decreased in the substantia nigra and striatum of mice after MPTP treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Although BFP contains phytoestrogens such as ginseng 37) that may act similarly to estrogen, which has been shown to prevent neuronal degeneration caused by increased oxidative stress 38) and apoptosis 39) ; other component herbs of BFP may act through different mechanisms, the details of which remain to be elucidated. Consistent with our research, TH and DAT gene expression 40,41) and protein patterns 41,42) of dopaminergic neurons have also been described by the other researchers. The intensity of TH-and DAT-immunoreactive dopaminergic cell bodies and terminals was also decreased in the substantia nigra and striatum of mice after MPTP treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Along these lines, a number of studies have demonstrated that estrogen is neuroprotective in 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced nigrostriatal lesions, an animal model of idiopathic PD [130][131][132][133][134][135][136][137][138][139][140]. Estrogen prevented MPTP-induced depletion of striatal dopamine, dopamine transporter binding and expression, decreased the MPTP-induced tyrosine hydroxylase-immunoreactive neuron loss and attenuated the glial activation induced by MPTP [130][131][132][133][134][135][136][137][138][139][140]. The estrogenic steroid principally used in these studies was 17β-estradiol (E2), and its effect on dopamine loss was shown by several studies to be stereospecific, as an isomer with weak estrogenic activity, 17α-estradiol, was ineffective at preventing MPTP-induced dopamine loss [131][132][133].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…25) In addition, as shown in Table 3, the levels of DA, DOPAC, 3-MT, HVA and 5-HT in the control mouse striatum measured by the HPLC-ECD method revealed significantly different values in different experiments, which are possibly due to different electrochemical behaviors and effects of analytes under different applied potentials and mobile phase compositions. [26][27][28]30,31) For example, the levels of DA reported by different workers were approximately in the range of 11 to 110 ng.…”
Section: Application Of the Methods To Real Biological Samplesmentioning
confidence: 98%
“…[25][26][27][28] However, the HPLC-ECD method has low sensitivity and serious limitations in the simultaneous determination of monoamines such as 5-HT, DA and DOPAC. 29) Under the standard separation protocols, the HPLC-ECD method requires two different mobile phases along with two separated HPLC-ECD systems for measuring the levels of 5-HT, DA and their metabolites.…”
Section: Application Of the Methods To Real Biological Samplesmentioning
confidence: 99%